Successful treatment with brigatinib in a patient with ALK-rearranged lung adenocarcinoma who developed crizotinib-induced interstitial lung disease. (May 2018) - Doménech, Marta; Jové, Maria; Aso, Samantha; Marín, Mar; Nadal, Ernest
Highlights: Interstitial lung disease (ILD) is potentially life-threatening event related with crizotinib. Incidence of crizotinib-related ILD was 1.2% and predisposing factors are unknown. Crizotinib rechallenge should be considered only in mild cases of ILD. Switching treatment to other ALK inhibitors was reported without ILD recurrence. Abstract: We present a 45-year-old patient diagnosed with anaplastic lymphoma kinase (ALK)-rearranged metastatic lung cancer who developed grade 4 interstitial lung disease (ILD) while on crizotinib treatment and was lately treated with brigatinib with no reappearance of ILD. To our knowledge, this is the first case report of successful treatment with brigatinib after crizotinib-induced ILD. Even though ILD secondary to brigatinib has been reported in clinical trials, no pulmonary toxicity has been seen in our patient, suggesting no crosslink lung toxicity between crizotinib and brigatinib.